Reporting and recording bias crime in New South Wales. Issue 2 (3rd April 2019) - Mason, Gail; Stanic, Rachael
ABSTRACT: This article presents the findings of the first study of official bias crime data held by the New South Wales Police Force. The purpose of this study was to unearth the institutional policies, procedures and practices that frame the response of the New South Wales Police Force to the reporting and recording of bias crime. While several overall patterns and trends are discernable in the bias crime data, their real significance lies in what they tell us about challenges for law enforcement in the dual process of reporting and recording bias crime. The article draws on qualitative interviews with New South Wales Police Force personnel to argue that a sustained program of capacity building and community engagement is needed if bias crime data is to provide meaningful intelligence on the nature of the problem and inform law enforcement responses.